A visible-light photoinduced charge-transfer complex promoted the ring opening of N-alkyl-4-piperidinols. Issue 7 (23rd March 2020) - Fu, Ying; Shi, Chun-Zhao; Xu, Qin-Shan; Du, Zhengyin; Huo, Congde
Abstract : ( E )-Homoallylamines are efficiently prepared through visible-light photoinduced charge-transfer complex promoted ring-opening of N -alkyl-4-piperidinols. Abstract : A visible-light photoinduced ring opening of N -alkyl-4-piperidinols under mild conditions has been achieved. The reaction sequence involves a visible-light-induced charge-transfer complex, which promoted the S–Cl bond cleavage of sulfonyl chlorides. The generated sulfonyl radical further reacts with N -alkyl-4-piperidinol cation radicals to achieve C–N and C–C bond cleavages to yield homoallylamine products.